A Simplified Approach in Estimating Technical Losses in Distribution Network Based on Load Profile and Feeder Characteristics - Au M.T.; Anthony T.M.; Kamaruddin N.; Verayiah R.; Mustaffa S.A.S.; Yusoff M. (2023)
This paper presents an approach to estimate technical losses of a large utility distribution network based on feeder load factor and feeder characteristics, such as feeder length, peak demand to installed capacity ratio, and load distribution profile along feeder. In this approach, feeders with different load distribution profile are modeled and simulated to establish generic peak power loss functions in three dimensions. A weighted average based on energy distribution along each feeder or network component (e.g distribution transformer) is then used to calculate the percentage technical losses for the whole network. The main advantages of this approach is it requires minimum set of input data which are commonly available in most utility distribution offices, while giving reasonably accurate results. The approach implemented with a spread sheet format is suitable for a quick energy auditing of existing distribution network technical losses as well as assessing sensitivity of distribution network efficiency to change in different network and load parameters. 2008 IEEE.